“Pasti Ke Singkawang!”: Tourism-Oriented City Branding and the Role of Local Government in Promoting Sustainable Cultural Tourism - Kevin Gustian Yulius; Sofiani Sofiani; Jimmy Muller Hasoloan Situmorang (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the implementation of tourism-oriented city branding in Singkawang and the role of local government in promoting sustainable cultural tourism through community participation. As one of Indonesia’s most multicultural cities, Singkawang has introduced the brand “Pasti Ke Singkawang!” to position itself as a unique and attractive destination. The research adopts a qualitative case study approach, combining interviews, field observations, and document analysis. The findings reveal that while the branding initiative has increased tourist visibility, it remains largely top-down and event-focused. Key challenges include limited integration of communal cultural assets, lack of grassroots involvement, and untapped potential in using intellectual property tools such as Geographical Indications (GI). Comparisons with other Indonesian cities—Yogyakarta, Solo, Denpasar, and Pekalongan—highlight the importance of community engagement, cultural protection, and institutional innovation in sustainable tourism branding. The study concludes that Singkawang’s brand can be strengthened by transforming it into a participatory platform that supports local creatives, protects intangible heritage, and integrates place-based cultural products into tourism strategies. This research contributes conceptually to the discourse on city branding as a tool for inclusive governance and sustainable development.